Wortbildung der deutschen Nomina instrumenti und ihre Äquivalente im Polnischen - Zdrojewski, Wojciech (Studia Germanica Posnaniensia, 2018)
The article presents results of confrontation of nouns in the German language included in the semantic class defined by the term "nomina instrumenti" with their Polish equivalents. On the basis of analysis of word formation structure the author performed a unilateral type of confrontation and the point of departure was the German language. Its foundation was the vocabulary taken from E. Mater's index a tergo “Rückläufiges Wörterbuch der deutschen Gegenwartssprache” and Polish equivalents were taken from “The Great German-Polish Dictionary” and “Scientific-Technical Dictionary of German and Polish”. The confrontation of German "nomina instrumenti" and their Polish equivalents was carried out according to word formation types represented in German, i. e. derivation, compounds and compound-derivative formations. The unilateral character of confrontation does not allow for a comprehensive treatment of this problem which points to the necessity of bilateral analysis.